2015
DOI: 10.1159/000369470
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease Is a Risk Factor for Severity of Organizing Pneumonia

Abstract: Background: The link between organizing pneumonia (OP) and gastroesophageal reflux disease (GERD) is not well known. There is little evidence in the literature to establish a causal link between GERD and OP. Objectives: The aim of the study was to assess the hypothesis that OP is more severe when it is associated with GERD and that it leads to more frequent relapses. Methods: In a retrospective study on 44 patients suffering from OP, we compared the clinical, radiological and histological characteristics of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…About 33% of patients who are treated for less than one year with corticosteroids experience recurrence. 13 Studies have shown that relapse is associated with multiple factors such as gastroesophageal reflux disease, a decrease in functional vital capacity, a decrease in serum protein, and severity of illness at diagnosis. 2,14,15 Lazor et al studied relapses in 48 cases and found that a delay in initial diagnosis was also associated with an increase in relapse.…”
Section: Discussionmentioning
confidence: 99%
“…About 33% of patients who are treated for less than one year with corticosteroids experience recurrence. 13 Studies have shown that relapse is associated with multiple factors such as gastroesophageal reflux disease, a decrease in functional vital capacity, a decrease in serum protein, and severity of illness at diagnosis. 2,14,15 Lazor et al studied relapses in 48 cases and found that a delay in initial diagnosis was also associated with an increase in relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In the last issue of Respiration , Gaillet et al [1] report on the significance of gastroesophageal reflux disease (GERD) as a risk factor for the severity of organizing pneumonia (OP). In their series, patients with OP and GERD had more extensive radiological involvement, greater hypoxemia and greater bronchoalveolar lavage cellularity compared to those with OP in the absence of GERD.…”
mentioning
confidence: 99%
“…BOOP as a manifestation of aspiration rather than rejection has also been reported after lung transplantation [27]. The study by Gaillet et al [1] examined the association between OP and GERD more closely. The prevalence of GERD in the study population was 45%, which exceeds the 20-30% seen in the general population.…”
mentioning
confidence: 99%
See 2 more Smart Citations